33PCombination of mTOR inhibition and paclitaxel as a personalised strategy in the context of MYC-amplified high-grade serous ovarian cancer. (7th November 2019) - Martins, F C; Couturier, D-L; de Santiago, I; Vias, M; Sanders, D; Piskorz, A; Hall, J; Jimenez-Linan, M; Hosking, K; Crawford, R; Brenton, J
Abstract: Background: The extreme genomic heterogeneity of high-grade serous ovarian carcinoma (HGSOC) is a major barrier to precision medicine approaches. We have developed mutational signature analysis from shallow whole genome sequencing (sWGS) for molecular stratification and therapeutic prediction. PARP inhibitor therapy has significant survival advantage for women with germline BRCA1/2 mutations, but treatments and predictive biomarkers for women without homologous recombination deficiency have not been developed. MYC amplification is the most common driver in HGSOC, present in 42% of the TCGA cases. The best responder from the phase 1 trial of AZD2014 (dual m-TORC1/2 inhibitor) and paclitaxel in HGSOC had a mutation in MYC and we have hypothesised that biosynthetic effects of MYC are mediated through the mTOR pathway and blocked by AZD2014 perturbation. Methods: Primary ovarian cancer spheroids were purified from 28 human ascites and profiled with sWGS. Ex-vivo therapeutic response was measured to four standard of care chemotherapeutic agents and eight inhibitors targeting nodal points of the PI3K and DNA damage repair pathways. RNA seq data from the TCGA HGSOC cohort was used to establish the genes whose expression was highly correlated with the expression of MYC. Results: Ex-vivo assays were predictive of first-line clinical response to chemotherapy agents (P < 0.001). 11/19 (58%) HGSOC spheroid samples showed significantly reduced viability with dual mTOR inhibition (AZD2014). MYC amplification was associated with AZD2014 and paclitaxel response. Expression of MYC and mTOR genes are strongly correlated in TCGA data. Conclusions: Our results suggest that therapeutic strategies combining paclitaxel and inhibition of mTOR pathway can be used as personalised treatment in the context of MYC-amplified HGSOC. We are currently examining gene expression after AZD2014 pertubation in HGSOC models and performing the genomic analysis of cases from the phase 1 trial of AZD2014 and paclitaxel. Legal entity responsible for the study: The authors. Funding: Academy of Medical Sciences, Addenbrookes Charitable Trust, Cancer Research UK, University of Cambridge. Disclosure: F.C. Martins: Research grant / Funding (self), The Clinical Lectureship from the Experimental Medicine Initiative is partly funded by AstraZeneca: AstraZeneca. All other authors have declared no conflicts of interest.